2017
DOI: 10.1186/s40359-017-0172-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in motivation and adherence to a prescribed assignment after face-to-face and online psychoeducation: an experimental study

Abstract: BackgroundAdherence to treatment homework is associated with positive outcomes in behavioral psychotherapy but compliance to assignments is still often moderate. Whether adherence can be predicted by different types of motivation for the task and whether motivation plays different roles in face-to-face compared to online psychotherapy is unknown. If models of motivation, such as Self-determination theory, can be used to predict patients’ behavior, it may facilitate further research into homework promotion. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 57 publications
1
21
0
1
Order By: Relevance
“…Across various therapeutic situations, autonomous motivation has been associated with more sustained behavior change (Alfonsson, Johansson, Uddling, & Hursti, 2017;Koponen, Simonsen, & Suominen, 2017), while controlled motivation has been shown to inconsistently interfere with change (Eisenberg, Lipsky, Dempster, Liu, & Nansel, 2016). In ED research, autonomous motivation has been related to greater improvement in ED symptoms, whereas controlled motivation has not been found to influence ED-symptom change (Carter & Kelly, 2015;Mansour et al, 2012;Steiger et al, 2017;Thaler et al, 2016;van der Kaap-Deeder et al, 2014), although trend-level effects have been observed .…”
Section: Introductionmentioning
confidence: 99%
“…Across various therapeutic situations, autonomous motivation has been associated with more sustained behavior change (Alfonsson, Johansson, Uddling, & Hursti, 2017;Koponen, Simonsen, & Suominen, 2017), while controlled motivation has been shown to inconsistently interfere with change (Eisenberg, Lipsky, Dempster, Liu, & Nansel, 2016). In ED research, autonomous motivation has been related to greater improvement in ED symptoms, whereas controlled motivation has not been found to influence ED-symptom change (Carter & Kelly, 2015;Mansour et al, 2012;Steiger et al, 2017;Thaler et al, 2016;van der Kaap-Deeder et al, 2014), although trend-level effects have been observed .…”
Section: Introductionmentioning
confidence: 99%
“…Also, the addressing of beliefs and needs of participants in form of a tailored and complaint-centred IMI program might strengthen treatment credibility. Intrinsic motivation and treatment credibility have been shown to positively relate to treatment adherence [34, 35]. Thereby, this complaint-based approach might be able to improve the overall impact of preventive internet-based interventions in routine health care by a) increasing the uptake of a preventive IMI program and b) by improving adherence to the IMI program.…”
Section: Discussionmentioning
confidence: 99%
“…Low adherence and high dropout rates [32, 33] restrict impact of IMIs. Treatment credibility and treatment motivation have been shown to predict treatment adherence [34, 35]. Thus, measures to increase motivation or treatment credibility are highly desirable, as they improve participation in preventive interventions and reduce dropout rates of participants [3639].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying variables that predict adherence is important in order to identify engaging features of interventions, to improve the content and design of our interventions and to identify participants who need a higher level of support to enable them to adhere to an intervention sufficiently. Intervention characteristics that have previously been linked to adherence include treatment credibility (Alfonsson et al, 2017; Alfonsson et al, 2016; El Alaoui et al, 2015b; Melville et al, 2010), the provision of guidance (Brouwer et al, 2011; Geraghty et al, 2010; Robinson et al, 2010; Wangberg et al, 2008; Zarski et al, 2016), peer support (Graham et al, 2017), regular updates of the intervention (Brouwer et al, 2011), the duration of the intervention (Cugelman et al, 2011), tailoring (Couper et al, 2010), the use of persuasive system design elements (Kelders et al, 2012), and periodic prompts (Beintner and Jacobi, 2017; Fry and Neff, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Participant characteristics that have previously been linked to adherence include baseline symptom severity (Christensen et al, 2009; Melville et al, 2010), age (Buller et al, 2008; Christensen et al, 2009; Melville et al, 2010; Wangberg et al, 2008), gender (Christensen et al, 2009; El Alaoui et al, 2015b; Kelders et al, 2013; Melville et al, 2010; Wangberg et al, 2008), marital status (Christensen et al, 2009; Melville et al, 2010), level of education (Alfonsson et al, 2016; Melville et al, 2010; Wangberg et al, 2008), outcome expectancy (Crutzen et al, 2011; Geraghty et al, 2010), locus of control (Geraghty et al, 2010), intrinsic motivation (Alfonsson et al, 2017; Alfonsson et al, 2016), and amount of internet use (Kelders et al, 2013). We aim to investigate the impact of a variety of interventions and participants characteristics on multiple aspects of adherence within and across interventions.…”
Section: Introductionmentioning
confidence: 99%